City size and functional specialization as factors of smart management: A case of Lviv Oblast, Ukraine : ст. - Lozynskyy, R.; Hrymak, O.; Kushnir, L.; Terletska, О.; Vovk, М. (Problems and Perspectives in Management, 2021)
The process of understanding the factors that affect the implementation of smart management in cities is pivotal for using this concept to improve the well-being of the population. The goal of this study is to establish the specifics of the implementation of the smart management concept in cities with different sizes and functional specialization. 44 cities of Lviv Oblast (Ukraine) are selected for this goal. The main method was a content analysis of information sources related to the activities of local authorities. The most important indicators that reflect the development of various components of a smart city are analyzed. It is established that measures for the introduction of smart technologies are carried out in most cities of the Oblast (about 80%). The leading cities are Lviv and Drohobych, among other cities are Boryslav, Truskavets, and Zolochiv. The share of cities with a high level of implementation of smart management technology is only 4%. However, 56% of the total urban population lives in these cities. Other cities are the smallest cities that did not have the functions of district centers. The share of such cities is 20% but only 3% of the population inhabits them. Among the components of the smart city concept, e-government tools are being most actively developed, followed by energy efficiency measures. There is no direct relationship between the size of cities and the implementation of smart technologies. Smart technologies are most intensively implemented in cities focused on tourism development. Former industrial cities are less successful.
Keywords: розумне управління містом; менеджмент і адміністрування; smart management; smart initiatives; smart city; e-government